INNOVATION OF SHARIA FINTECH: HALAL FINANCING SOLUTIONS IN THE ERA OF DIGITAL ECONOMY - Helma Maraliza (Adisam Publisher, 2025)
The global economic transformation driven by advances in digital technology has encouraged the birth of various innovations in the financial sector, one of which is financial technology (fintech). In the context of Islamic economics, the emergence of sharia fintech has become an alternative financing that offers halal solutions and is in accordance with sharia principles. This study aims to examine the role of sharia fintech innovation in providing halal financing solutions in the digital economy era. The method used in this study is a literature review, by collecting and analyzing various scientific sources such as journals, books, industry reports, and regulations related to sharia fintech. The results of the study show that sharia fintech has great potential in increasing sharia financial inclusion, expanding access to financing for the community, and strengthening the overall Islamic economic ecosystem. Innovations in the form of sharia peer-to-peer lending, sharia-based crowdfunding, and sharia digital wallets are real examples of technological adaptation that still prioritize the principles of justice, transparency, and free from usury. However, there are still challenges in terms of regulation, sharia financial literacy, and digital infrastructure readiness. Therefore, synergy between regulators, industry players, and academics is needed to optimize the role of sharia fintech as a halal financing solution in the digital era.